Alternative to sustain the biodiversity of orchid species. (Hombre, Ciencia y Tecnología, 2018)
The work was carried out at the Mountain Development Center located in El Salvador municipality, Guantánamo province, with the objective of restoring the Orquideario "Celia Sánchez Manduley" affected by Hurricane Sandy. As a part of the study, a set of activities was carried out in the period from March to December 2016, thus resulting in the restoration of 0.2 hectares with 1022 adapted specimens of different epiphytic and terrestrial orchid species existing in mountainous areas of Guantánamo. In addition to this, 42 specimens of fruit species were established for the reforestation of the area and as a substrate for epiphytic species.